2021
DOI: 10.1002/pssb.202100159
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Studies of Metals with Complex Order by means of the Optical Floating‐Zone Technique

Abstract: The availability of large high‐quality single crystals is an important prerequisite for many studies in solid‐state research. The optical floating‐zone technique is an elegant method to grow such crystals, offering potential to prepare samples that may be hardly accessible with other techniques. As elaborated in this report, examples include single crystals with intentional compositional gradients, deliberate off‐stoichiometry, or complex metallurgy. For the cubic chiral magnets Mn1–xFexSi and Fe1–xCoxSi, sing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 96 publications
1
6
0
Order By: Relevance
“…[21,65] For our study, we chose the itinerant-electron antiferromagnet CrB 2 with its rather low Néel temperature T N ¼ 88K, as high-purity single crystals grown by means of optical floating-zone technique were available. [66][67][68] The samples investigated under pressure were cut from the same ingots for which the transport and thermodynamic properties as well as quantum oscillatory and neutron scattering studies were reported previously. [21,69,70] In our study, three different pressure cells were used, notably a piston-cylinder cell for pressures up to 2.2 GPa, a uniaxial pressure cell for pressures up to 0.5 GPa, and a Bridgman cell for measurements up to 8 GPa.…”
Section: Incipient Superconductivity In Crbmentioning
confidence: 99%
See 1 more Smart Citation
“…[21,65] For our study, we chose the itinerant-electron antiferromagnet CrB 2 with its rather low Néel temperature T N ¼ 88K, as high-purity single crystals grown by means of optical floating-zone technique were available. [66][67][68] The samples investigated under pressure were cut from the same ingots for which the transport and thermodynamic properties as well as quantum oscillatory and neutron scattering studies were reported previously. [21,69,70] In our study, three different pressure cells were used, notably a piston-cylinder cell for pressures up to 2.2 GPa, a uniaxial pressure cell for pressures up to 0.5 GPa, and a Bridgman cell for measurements up to 8 GPa.…”
Section: Incipient Superconductivity In Crbmentioning
confidence: 99%
“…[ 21,65 ] For our study, we chose the itinerant‐electron antiferromagnet CrB2 with its rather low Néel temperature TnormalN=88K, as high‐purity single crystals grown by means of optical floating‐zone technique were available. [ 66–68 ] The samples investigated under pressure were cut from the same ingots for which the transport and thermodynamic properties as well as quantum oscillatory and neutron scattering studies were reported previously. [ 21,69,70 ]…”
Section: Incipient Superconductivity In Crb2mentioning
confidence: 99%
“…Namely, when using a seed crystal with the T element appropriate for the desired handedness, the single crystal with the selected handedness is obtained. [34][35][36] For instance, a right-handed CoSi can be grown by using a right-handed FeSi as a seed crystal. Such ideas of the chirality-controlled crystal growth were indeed demonstrated in a Czochralski method 34) and in a floating zone (FZ) method.…”
Section: Introductionmentioning
confidence: 99%
“…Such ideas of the chirality-controlled crystal growth were indeed demonstrated in a Czochralski method 34) and in a floating zone (FZ) method. 35,36) Intermetallic disillicide compounds TSi 2 with a C40 type chiral hexagonal crystal structure are the next target materials for chirality-controlled crytal growth. Recently, TSi 2 is found to show the CISS effect.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the emergence of a high-mobility surface conduction channel at low temperatures was inferred from the electrical transport properties of a series of single crystals of FeSi prepared under systematic variation of the initial iron content using the optical floating-zone technique [19][20][21][22][23]. This observation was corroborated by means of measurements on thin needles grown from tin flux [24] as well as high-resolution tunneling spectroscopy that revealed two in-gap states in the low-temperature regime of the samples grown by the floating-zone technique [25].…”
Section: Introductionmentioning
confidence: 99%